= 6(4x - 5) + 2(3x + 4)
= (6 × 4x) - (6 × 5) + (2 × 3x) + (2 × 4)
= 24x - 30 + 6x + 8
= (24x + 6x) - (30 - 8)
= 30x - 22
Jawaban:
30x - 22
Penjelasan dengan langkah langkah:
6(4x - 5) + 2(3x + 4)
= 24x + 6x - 30 + 8
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
= 6(4x - 5) + 2(3x + 4)
= (6 × 4x) - (6 × 5) + (2 × 3x) + (2 × 4)
= 24x - 30 + 6x + 8
= (24x + 6x) - (30 - 8)
= 30x - 22
Jawaban:
30x - 22
Penjelasan dengan langkah langkah:
6(4x - 5) + 2(3x + 4)
= 24x - 30 + 6x + 8
= 24x + 6x - 30 + 8
= 30x - 22